Effects of rootstocks on the bud-take, growth and development of some Turkish and foreign pistachio cultivars under Kahramanmaras ecological conditions - Kaska N.; Nikpeyma Y. (XI GREMPA Seminar on Pistachios and Almonds, 2001)
In Turkey pistachio nut yield per tree is quite low. In order to improve it a comprehensive experiment was designed by taking varieties, rootstocks, pollinators and irrigation into consideration. In this paper the effects of the rootstocks on the bud-take and the growths of the scions will be presented.
11. GREMPA Seminar on Pistachios and Almonds, 1999/09/01-04, Sanliurfa (Turkey)